Factor Analysis of a Diagnostic Test for Mathematics Learning Difficulties Using Exploratory Factor Analysis (EFA) - Apri Triana; Tri Windi Oktara (Publikasi Indonesia, 2026)
The development of a diagnostic test for mathematics learning difficulties aims to identify the domains in which students demonstrate the lowest level of mastery. By identifying the domains in which students experience the greatest difficulties, targeted improvements can be implemented more effectively. Therefore, this study analyzes the dominant factors within a diagnostic test that was developed based on mathematical domains. The purpose of this study is to identify the factors within the mathematics domains that have been operationalized in the form of a test instrument. The resulting factors are formed from the correlations among items used to measure students’ abilities. Each factor formed must contain at least one mathematical domain represented in the test items. In some cases, a factor may consist of more than one mathematical domain. The identified factors represent the mathematical problem-solving abilities of the test participants. This study employed an exploratory descriptive research method. The research describes the characteristics of the analysis results using Exploratory Factor Analysis (EFA). The calculations were performed using SPSS software, and the resulting output was interpreted according to the characteristics of EFA. The research sample consisted of responses from 323 students. These responses represented answer choices for a diagnostic test comprising 30 questions with five alternative answers for each item. The results of the data analysis identified four mathematical domains, namely Algebra, Calculus, Geometry, and Trigonometry. Furthermore, the analysis of the diagnostic test on students’ mathematics learning difficulties revealed nine dominant factors